2017
DOI: 10.3389/fnhum.2017.00439
|View full text |Cite
|
Sign up to set email alerts
|

Affective Processing in Non-invasive Brain Stimulation Over Prefrontal Cortex

Abstract: The prefrontal cortex (PFC) is the most frequently targeted brain region by non-invasive brain stimulation (NBS) studies. Non-invasively stimulating the PFC has been shown to both modulate affective processing and improve the clinical symptoms of several psychiatric disorders, such as depression and schizophrenia. The magnitude of the modulation depends on several factors, including the stimulation frequency, the number of stimulation sessions, and the specific sub-region of the PFC that is stimulated. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 103 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…This may be due to differences in the participants and experimental setups in the two previous studies and our study (the presentation of emotionally negative and neutral pictures as well as psychosocial stress situation in the previous and competitive situation in the present study). Accordingly, an increase in the activity DLPFC may affect the HPA axis through the modulation of the neural activity of subcortical structures, such as the amygdala (Liu et al, 2017). Several lines of evidence have suggested that the impact of tDCS on the HPA axis may occur by a top-down modulation.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to differences in the participants and experimental setups in the two previous studies and our study (the presentation of emotionally negative and neutral pictures as well as psychosocial stress situation in the previous and competitive situation in the present study). Accordingly, an increase in the activity DLPFC may affect the HPA axis through the modulation of the neural activity of subcortical structures, such as the amygdala (Liu et al, 2017). Several lines of evidence have suggested that the impact of tDCS on the HPA axis may occur by a top-down modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Another brain region that has been considered a key region in emotion regulation (Mayberg et al, 1999 ) and that has recently been investigated as a new rTMS target for depression is the dorsomedial prefrontal cortex (DMPFC; i.e., DMN node; Downar and Daskalakis, 2013 ; Anderson et al, 2016 ; Liu S. et al, 2017 ; Liu W. et al, 2017 ). Studies have suggested that rTMS targeting the DMPFC could show similar antidepressant findings in patients with depression and is a safe procedure (e.g., Downar et al, 2014 ; Salomons et al, 2014 ; Bakker et al, 2015 ).…”
Section: Various Stimulation Targets For a Specific Disordermentioning
confidence: 99%
“…Differences in the experimental setups such as the number and duration of tACS sessions, stimulation parameters (frequency, intensity, duration, etc.) and the specific sub-region of the cortex that is stimulated are factors that influence the tACS entrainment effect ( Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%